Purchase Decision of Club Brand Mineral Water: The Influence of Price, Quality, and Promotion in Jabodetabek - Ramdani, Remi; Saputra, Fendi (Baileo: Jurnal Sosial Humaniora, 2025)
Purchase decision is a crucial aspect of marketing strategy, especially in the highly competitive mineral water industry. This study aims to analyze the influence of price, product quality, and promotion on the purchase decision of Club brand mineral water in the Jabodetabek area. The research employs a quantitative approach by collecting primary data through a questionnaire distributed via Google Forms. The study sample consists of 125 respondents who are Club mineral water consumers in Jabodetabek, selected using purposive sampling. Data analysis was conducted through respondent characteristic tests, descriptive statistical analysis, multiple linear regression analysis, normality tests, t-tests, F-tests, and hypothesis testing. The results indicate that price does not have a significant influence on purchase decisions, as evidenced by a significance value of 0,065, which exceeds the 0,05 threshold, and a t-value of 1,864, which is smaller than the t-table value (1,979). Conversely, product quality is proven to have a significant influence on purchase decisions, with a significance value of 0,006 and a t-value of 2,822, which exceeds the t-table value. The promotion factor also has a significant influence, with a significance value of 0,000 and a t-value of 5,036. These findings suggest that consumers prioritize product quality and the effectiveness of promotions over price when making purchase decisions for Club brand mineral water. The novelty of this study lies in its specific analysis of consumer preferences within the mineral water product category in Jabodetabek, as well as the role of promotion as a more dominant determinant of purchase decisions compared to price. The implications of this study provide recommendations for marketing strategy developers, particularly in the bottled beverage industry, to focus more on quality improvement and promotional innovation to attract consumers. From a social sciences and humanities perspective, these findings contribute to consumer behavior studies within the context of microeconomics and value perception-based marketing strategies.